What is the effectiveness of chiropractic manipulation compared to standard physical therapy in reducing pain intensity and improving functional mobility for patients with chronic low back pain? : A Systematic Review - Satya Agung Nugroho; Nazalla Gwen Vaganesha; Hasnan Habib Afifudin (International Medical Journal Corp. Ltd, 2025)
Introduction : Chronic low back pain (CLBP) is a pervasive health issue that significantly impairs quality of life and functional capacity globally. Among non-pharmacologic interventions, chiropractic manipulation and standard physical therapy are common treatments. This systematic review aims to compare the effectiveness of these two modalities in reducing pain intensity and improving functional mobility for adults with CLBP. Methods : This systematic review adhered to the PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar to identify randomized controlled trials, systematic reviews, and meta-analyses. Studies were included if they compared chiropractic manipulation by licensed chiropractors to standard physical therapy for adult patients with CLBP lasting over 12 weeks. Primary outcomes included pain intensity and functional mobility measured by validated scales. Results Eighteen studies were included in the final analysis. The results indicate that chiropractic manipulation and standard physical therapy are largely equivalent in effectiveness for both pain reduction and functional improvement. While a few studies reported superior short-term pain relief with spinal manipulative therapy , most found no significant long-term differences between the two interventions. Adverse events associated with both treatments were infrequently reported and were generally mild and transient. Discussion: The evidence demonstrates a consistent pattern of equivalence in clinical outcomes between chiropractic care and physical therapy. This suggests that neither modality is definitively superior for the majority of CLBP patients. The significant variability in treatment protocols across studies highlights the need for individualized care plans. Patient characteristics did not reliably predict a differential response to either therapy, underscoring the importance of shared decision-making. Conclusion: Chiropractic manipulation and standard physical therapy are both effective and safe interventions for managing chronic low back pain, yielding comparable outcomes. The choice between these treatments should be guided by patient preference, accessibility, and clinical presentation. An integrative approach, potentially combining the strengths of both disciplines, may further enhance patient care.